2010
DOI: 10.1021/jp912201h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Spray Pyrolysis Synthesis of Porous Bi2WO6 Microspheres and Their Visible-Light-Induced Photocatalytic Removal of NO

Abstract: In this study, porous Bi2WO6 microsphere photocatalysts were obtained via the ultrasonic spray pyrolysis method using bismuth citrate and tungstic acid as precursors in basic aqueous solution. The characteristics of the resulting samples were investigated in detail by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, N2 adsorption/desorption, X-ray photoelectron spectroscopy, and UV−vis diffuse reflectance spectroscopy. The resulting porous Bi2WO6 microsphere was of high crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(110 citation statements)
references
References 32 publications
7
102
0
1
Order By: Relevance
“…To the best of our knowledge no study has been reported on the photocatalytic removal of NO x using Bi 2 Mo 3 O 12 as photocatalyst. However, the isostructural tungstate phase of Bi 2 MoO 6 , with chemical formula Bi 2 WO 6 was reported for NO removal under visible and solar light irradiation [16]. In the current work, the photocatalytic activity of Bi 2 Mo 3 O 12 oxide was tested under UVA irradiation for NO removal from air under different experimental conditions.…”
Section: Introductionmentioning
confidence: 88%
“…To the best of our knowledge no study has been reported on the photocatalytic removal of NO x using Bi 2 Mo 3 O 12 as photocatalyst. However, the isostructural tungstate phase of Bi 2 MoO 6 , with chemical formula Bi 2 WO 6 was reported for NO removal under visible and solar light irradiation [16]. In the current work, the photocatalytic activity of Bi 2 Mo 3 O 12 oxide was tested under UVA irradiation for NO removal from air under different experimental conditions.…”
Section: Introductionmentioning
confidence: 88%
“…Numerous methods have been employed to fabricate 0-D PCs including coprecipitation or chemical precipitation, hydrothermal/solvothermal process [19,20], sol-gel, solid state reaction (SSR), spray pyrolysis [21][22][23], combustion [24,25], reversemicroemulsion [26,27], and modified approaches based on them. The morphology and performance of photocatalyst crystal intensely depend on the synthesis 3 .…”
Section: -Dimensional: Quantum Dots Nano-/micro-particlesmentioning
confidence: 99%
“…40 nm. In addition, by the ultrasonic spray pyrolysis (USP) method instead of hydrothermal process, Lee group obtained Bi 2 WO 6 porous microspheres via using bismuth citrate and tungsten acid as precursors in basic aqueous solution [61].…”
Section: Flower/sphere-like Bi 2 Wo 6 Superstructuresmentioning
confidence: 99%